2018
DOI: 10.1007/s10815-018-1384-1
|View full text |Cite
|
Sign up to set email alerts
|

Lower follicular n-3 polyunsaturated fatty acid levels are associated with a better response to ovarian stimulation

Abstract: Objectives To analyze in detail the fatty acid (FA) composition of follicular fluid (FF) from two-sized follicles at oocyte retrieval and to determine associations of the FAs from large follicles with the woman's age and the response to ovarian stimulation. Design Observational study. Setting University and fertility clinic. Patients Sixty-four women (age 19-46), consisting of unfertile patients and oocyte donors, undergoing controlled ovarian stimulation. Interventions None. Main outcome measure(s) FF from sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Using a large cohort of New Zealand women ( n = ~ 1300) aged 15 to 65+ years, Crowe et al identified that concentrations of EPA and DHA in blood serum lipids increased with age (Crowe et al, 2008). Our findings of positive association of follicular fluid omega‐3 fatty acids with age, agree with previous description of such associations for EPA, DPA, and DHA (Ruiz‐Sanz et al, 2019). Higher omega‐3 fatty acids with age may relate to dietary or metabolic differences.…”
Section: Discussionsupporting
confidence: 93%
“…Using a large cohort of New Zealand women ( n = ~ 1300) aged 15 to 65+ years, Crowe et al identified that concentrations of EPA and DHA in blood serum lipids increased with age (Crowe et al, 2008). Our findings of positive association of follicular fluid omega‐3 fatty acids with age, agree with previous description of such associations for EPA, DPA, and DHA (Ruiz‐Sanz et al, 2019). Higher omega‐3 fatty acids with age may relate to dietary or metabolic differences.…”
Section: Discussionsupporting
confidence: 93%
“…In animals, there are many examples of diet and body composition influencing the FA content of FF (32), cumulus cells (33,34), and oocytes (34). In humans, the FA profile of FF changes as the follicle grows (35). Elevated FF levels of FAs have been associated with poor cumulusoocyte morphology (31).…”
Section: Discussionmentioning
confidence: 99%
“…As follicular fluid (FF) surrounds the maturing oocyte prior to fertilization, its characteristics can influence the outcome of assisted reproduction in terms of fertilization success, embryonic development, and pregnancy rate [ 13 ]. In FF, fatty acids (FA) play important roles as cellular energy sources, structural components of membranes, and precursors for prostaglandins and steroid synthesis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of O’Gorman et al [ 15 ] , non-cleaved oocytes (which fertilized normally but failed to cleave) showed an increased proportion of C16:0 in FF compared with oocytes which developed into early cleavage stage embryos, while the proportions of C18:0, C20:4n-6 and C22:6n-3 were lower. Ruiz-Sanz et al [ 13 ] showed that the levels of total n-3 polyunsaturated FA (PUFA), particularly C22:6n-3, as well as C20:4n-6 were significantly increased while lower levels of C18:3n-3 were noted in the FF of large compared to small follicles. However, investigations into the effect of FA available in the follicular environment on embryo development until day 5 are still lacking.…”
Section: Introductionmentioning
confidence: 99%